A General Strategy for Stretchable Microwave Antenna Systems using Serpentine Mesh Layouts. (16th October 2017) - Chang, Tammy; Tanabe, Yuji; Wojcik, Charles C.; Barksdale, Alex C.; Doshay, Sage; Dong, Zhenya; Liu, Hao; Zhang, Maoyi; Chen, Yuli; Su, Yewang; Lee, Thomas H.; Ho, John S.; et al.
Abstract: Wireless functionality is essential for the implementation of wearable systems, but its adaptation in stretchable electronic systems has had limited success. In this paper, the electromagnetic properties of stretchable serpentine mesh‐based systems is studied, and this general strategy is used to produce high‐performance stretchable microwave systems. Stretchable mechanics are enabled by converting solid metallic sections in conventional systems to subwavelength‐scale serpentine meshes, followed by bonding to an elastomeric substrate. Compared to prior implementations of serpentine meshes in microwave systems, this conversion process is extended to arbitrary planar layouts, including those containing curvilinear shapes. A detailed theoretical analysis is also performed and a natural tradeoff is quantified between the stretching mechanics and microwave performance of these systems. To explore the translation of these concepts from theory to experiment, two types of stretchable microwave devices are fabricated and characterized: a stretchable far‐field dipole antenna for communications and a stretchable midfield phased surface for the wireless powering of biomedical implanted devices. Abstract : A general strategy for producing high‐performance stretchable microwave systems using subwavelength‐scale serpentine mesh layouts is presented. A detailed theoretical analysis is used to quantify the natural tradeoff between the stretching mechanics and microwave performance of these systems. To explore the translation of these concepts from theory to experiment, a stretchable far‐field dipole antenna and midfield phased surface are demonstrated.